Estado trófico do açude Acarape do Meio com prognósticos usando modelagem matemática - Lima, Fernando Fernandes de (2007)
Eutrophication is a problem that is becoming more important within the scientific community that studies the aquatic ecosystems. Methods for a better understanding of the phenomenon are object of research since the 70´s, mostly through mathematical modeling. Being able to avoid the human and industrial use of a reservoir, eutrophication must be a reason for a everyday concern of water resources managers, as once it is set up, the time needed for recovery of a reservoir is usually no less than 10 years. At Fortaleza Metropolitan Region, the Acarape do Meio reservoir is one of the most important ones for industrial and human use, and its eutrophication process is intensifying during the last years. The local water resources management company (COGERH) is looking for ways to better understand the reservoir behavior through a constant monitoring campaign. Within this work it is made a report of the recent situation of Acarape do Meio, together with prognoses, obtained with the mathematical model of the PAMOLARE software, developed by the United Nations. Pollution limits were defined as an objective to revert the eutrophication process.